2015
DOI: 10.1088/0741-3335/57/4/044005
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of fast neutrons by magnetized deuterons in an optimized deuterium gas-puff z-pinch

Abstract: Z-pinch experiments with deuterium gas puffs have been carried out on the GIT-12 generator at 3 MA currents. Recently, a novel configuration of a deuterium gas-puff z-pinch was used to accelerate deuterons and to generate fast neutrons. In order to form a homogeneous, uniformly conducting layer at a large initial radius, an inner deuterium gas puff was surrounded by an outer hollow cylindrical plasma shell. The plasma shell consisting of hydrogen and carbon ions was formed at the diameter of 350 mm by 48 plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 58 publications
0
39
1
1
Order By: Relevance
“…Ion-ion Coulomb collision is considered with the use of MC method. In the model simulation, in the configuration close to described in [6], it was obtained the neutron yields up to 1.2×10 12 . Most neutrons are not thermonuclear.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Ion-ion Coulomb collision is considered with the use of MC method. In the model simulation, in the configuration close to described in [6], it was obtained the neutron yields up to 1.2×10 12 . Most neutrons are not thermonuclear.…”
mentioning
confidence: 83%
“…We present the hybrid MHD/PIC simulations of the time evolution of a deuterium gas puff z pinch. Recent experiments with 3-MA current pinches [6] made in a novel configuration have shown that the neutron yields can reach 3.6×10…”
Section: Related Contentmentioning
confidence: 99%
See 3 more Smart Citations